2011
DOI: 10.1089/bfm.2010.0076
|View full text |Cite
|
Sign up to set email alerts
|

Longer Previous Smoking Abstinence Relates to Successful Breastfeeding Initiation Among Underserved Smokers

Abstract: Objectives: The purpose of this study was to examine sociodemographic and behavioral factors related to successful breastfeeding initiation among medically underserved maternal smokers-a population with persistently low rates of initiation. Subjects and Methods: Pretreatment data from a larger randomized behavioral counseling, secondhand smoke reduction trial was examined for this study. Maternal smokers with babies younger than 4 years old reported breastfeeding behaviors. Mothers who breastfed for >4 weeks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…17 Similarly, in a smaller RCT of 54 women, Collins et al found that maternal smokers who remained abstinent were more likely to initiate breastfeeding postpartum. 7 In another RCT of 54 mothers of infants in the NICU, breastfeeding and maintenance of smoking cessation were both improved when mother-infant bonding was encouraged in the first 8 weeks postpartum. 18 Our study findings should be considered within the context of its limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Similarly, in a smaller RCT of 54 women, Collins et al found that maternal smokers who remained abstinent were more likely to initiate breastfeeding postpartum. 7 In another RCT of 54 mothers of infants in the NICU, breastfeeding and maintenance of smoking cessation were both improved when mother-infant bonding was encouraged in the first 8 weeks postpartum. 18 Our study findings should be considered within the context of its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing smoking cessation in the postpartum period may also provide an opportunity to promote breastfeeding because smoking is associated with higher formula-feeding rates. 7 We examined whether there was any association between smoking cessation and having an infant in the newborn nursery (NBN) versus the NICU. Additionally, we compared acceptance rates for quitline services between the 2 units and explored opportunities for improved smoking cessation interventions with parents of newborns in both units.…”
mentioning
confidence: 99%
“…In one Japanese study, maternal use of alcohol, controlled for numerous socioeconomic factors, was associated with an increased likelihood of continuing to breastfeed until 6 months (OR 1.5; but almost none was exclusive) (Inoue 2012). In contrast, in one German study (Logan et al 2016), women who resumed drinking by 6 weeks of age were twice as likely to have stopped breastfeeding by 6 months (HR 2.1) and those who had resumed drinking by 4 months (Little, Lambert, and Worthington-Roberts 1990); (Grossman et al 1989); (Collins, DiSantis, and Nair 2011); (van Rossem et al 2009); (Kim et al 2003); (Parackal, Ferguson, and Harraway 2007); (Butler et al 2004); (Weiser et al 2009); (Racine et al 2009); (Torris et al 2013); (Xu et al 2010); (Simard et al 2005); (Breslow et al 2007); (Tay et al 2017) 3 (Logan et al 2016); (Motee et al 2013); (Chaves, Lamounier, and César 2007) 2 (Inoue 2012); (Dozier, Nelson, and Brownell 2012) a This is almost always defined as routinely taking two drinks or less per day. In the US, "drink" is defined as containing 13.5g alcohol and in Australia 10g.…”
Section: Impact Of Alcohol Consumption On Breastfeeding Patternsmentioning
confidence: 91%
“…Women who have quit smoking for at least a month are more likely to initiate breastfeeding. 72 Additionally, women who quit smoking tend to continue breastfeeding for a longer period of time than those who continue to smoke. 73 Indeed, breastfeeding is still recommended by the National Health Service and the American Academy of Pediatrics, among others, because of its beneficial effects on the baby, even if the mother continues to smoke.…”
Section: Smoking and Breastfeedingmentioning
confidence: 99%